Utility of Peak Expiratory Flow Rate Monitoring in Diagnosing Exercise-Induced Bronchoconstriction in School-Aged Children - Mogili, Hemanth; Harivignesh, Harivignesh (Journal of Neonatal Surgery, 2025)
Background: Exercise-induced bronchoconstriction (EIB) is common in children but often underdiagnosed. The reference standard, exercise challenge testing with spirometry, is resource-intensive. Peak expiratory flow rate (PEFR) monitoring is simpler but its diagnostic accuracy in children is not well established. Methods: A prospective diagnostic study was conducted on 120 school-aged children (aged 6–14 years) with suspected EIB between January and March 2025. All children underwent a standardised 6-minute free-running exercise challenge. PEFR was measured before exercise and at 5, 10, 15, and 20 minutes post-exercise using a portable peak flow meter. Spirometry (FEV1) was performed at the same time points as the reference standard. A positive EIB diagnosis was defined as a ≥10% fall in FEV1 from baseline. Results: EIB was confirmed in 48 children (40.0%). A ≥15% fall in PEFR from baseline demonstrated sensitivity of 83.3% (95% CI: 69.8–92.5%) and specificity of 88.9% (95% CI: 79.3–95.1%) for diagnosing EIB. The optimal PEFR fall threshold was 12.5% (sensitivity 87.5%, specificity 84.7%). Negative predictive value was 88.9% at a 15% threshold. Children with asthma had higher rates of EIB (68% vs 18% in non-asthmatics, p<0.001). PEFR recovery to baseline by 20 minutes occurred in 79% of children. Conclusions: PEFR monitoring using a 15% fall threshold has good diagnostic accuracy for EIB in school-aged children and can be performed in schools or primary care settings where spirometry is unavailable. A negative PEFR test (fall <15%) effectively rules out clinically significant EIB.